Invariances : the structure of the objective world - Nozick, Robert (Cambridge, Mass. : Belknap Press of Harvard University Press, 2001)
Robert Nozick presents bold philosophical theories that take account of scientific advances in physics, evolutionary biology, economics and cognitive neuroscience, and casts contemporary cultural controversies in a new light
I. The structure of the objective world. 1. Truth and relativism -- 2. Invariance and objectivity -- 3. Necessity and contingency -- II. The human world as part of the objective world. 4. The realm of consciousness -- 5. The genealogy of ethics
Includes bibliographical references and index
Keywords: Relativity; Truth; Objectivity; Ethics; Necessity (Philosophy); Contingency (Philosophy); Consciousness; Ethics; Consciousness